11.6k views
5 votes
Which of these expressions is equal to 6 + (2 + 3) × 5? (4 × 5) + 3 9 × 5 + 10 5 + 4 × ( 5 - 6) 1 + 10 × 3 Flag Question Skip

1 Answer

2 votes

Answer:

The correct answer is:

1 + 10 × 3

Explanation:

using the rule of order of operations in mathematics, the order of operations from first precedence to last precedence are: parenthesis ( ), exponentiation and root extraction, multiplication and division, addition and subtraction. Therefore, the expression:

6 + (2 + 3) × 5 = 6 + 5 × 5 ( parenthesis)

= 6 + (5 × 5) = 6 + 25 ( multiplication)

= 6 + 25 = 31 (addition)

∴ 6 + (2 + 3) × 5 = 31.

Following this same rule, the expression:

1 + 10 × 3 = 1 + (10 × 3) (multiplication)

= 1 + 30 = 31 (addition)

User Leogreen
by
4.2k points